AGR256: Agricultural Research Methods / Faculty of Plantation and Agrotechnology - UiTM, Faculty of Plantation and Agrotechnology (Universiti Teknologi MARA (UiTM), 2017)
This course will introduce students to the research techniques in the conduct of field experimentation and factors affecting the outcomes of experimental results. Students will study the techniques of sampling, three types of experimentation designs, data collection including computing descriptive and inferential statistics. The student will compute descriptive statistics that include methods of data presentation, measurement of central tendency and dispersion. The student will also compute inferential statistics that include statistical tests based on normal distribution as well as chi-square tests, linear regression and the use of correlation coefficient.